Thermal Comfort Meets ESG Principle: A Systematic Review of Sustainable Strategies in Educational Buildings - Yujing Xiang; Pengzhi Zhou; Li Zhu; Shihai Wu (Buildings)
Securing thermal comfort while minimizing energy consumption in educational buildings is vital for achieving sustainable development goals. Drawing on the Environmental, Social, and Governance (ESG) framework, this systematic review synthesizes findings from 84 peer-reviewed studies published over the past decade, with a focus on how thermal comfort and energy use are assessed in educational contexts. The review identifies three primary research themes: climate resilience, multidimensional human-centric design, and energy decarbonization. However, it also reveals that existing studies have placed disproportionate emphasis on the environmental dimension, with insufficient exploration of issues related to social equity and governance structures. To address this gap, this study introduces an ESG-driven theoretical framework encompassing seven dimensions: thermal environment stability, multimodal thermal comfort assessment integration, sustainable energy use, heterogeneous thermal demand equality, passive–active design synergy, participatory thermal data governance, and educational thermal well-being inclusivity. By fostering interdisciplinary convergence and emphasizing inclusive stakeholder engagement, the proposed framework provides a resilient and adaptive foundation for enhancing indoor environmental quality in educational buildings while advancing equitable climate and energy strategies.